2009
DOI: 10.1186/1475-2840-8-37
|View full text |Cite
|
Sign up to set email alerts
|

Biliary pancreatic diversion and laparoscopic adjustable gastric banding in morbid obesity: their long-term effects on metabolic syndrome and on cardiovascular parameters

Abstract: BackgroundBariatric surgery is able to improve glucose and lipid metabolism, and cardiovascular function in morbid obesity. Aim of this study was to compare the long-term effects of malabsorptive (biliary pancreatic diversion, BPD), and restrictive (laparoscopic gastric banding, LAGB) procedures on metabolic and cardiovascular parameters, as well as on metabolic syndrome in morbidly obese patients.Methods170 patients studied between 1989 and 2001 were called back after a mean period of 65 months. 138 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 48 publications
1
18
0
2
Order By: Relevance
“…32,37 We found a specific decrease in plasma TC and LDL-C after GBP but not after SG. These findings are in keeping with other studies showing that mixed malabsorptive and restrictive surgery (GBP) is more effective than restrictive surgery (SG) in reducing cholesterol levels 37,38 and more specifically that TC and LDL-C are significantly reduced 12 months after GBP but not after SG. 39 In malabsorptive surgery, it has been shown that intestinal cholesterol absorption decreases leading to decreased plasma TC and LDL-C concentrations, accompanied by enhanced hepatic cholesterol synthesis and catabolism.…”
Section: Discussionsupporting
confidence: 81%
“…32,37 We found a specific decrease in plasma TC and LDL-C after GBP but not after SG. These findings are in keeping with other studies showing that mixed malabsorptive and restrictive surgery (GBP) is more effective than restrictive surgery (SG) in reducing cholesterol levels 37,38 and more specifically that TC and LDL-C are significantly reduced 12 months after GBP but not after SG. 39 In malabsorptive surgery, it has been shown that intestinal cholesterol absorption decreases leading to decreased plasma TC and LDL-C concentrations, accompanied by enhanced hepatic cholesterol synthesis and catabolism.…”
Section: Discussionsupporting
confidence: 81%
“…[126][127][128] As demonstrated in cohorts of 16 to 60 obese patients, there can be improvements in ventricular mass and diastolic function in the 3 months to 3.6 years after bariatric surgery in patients without baseline clinical cardiac disease. 110,[129][130][131][132] The most convincing improvements are seen in LV mass and mass index, E/A ratio, and isovolumic relaxation time. Importantly, the LV mass regression appears to be independent of postoperative systolic blood pressure changes.…”
Section: Left Ventricular Dysfunction Heartmentioning
confidence: 82%
“…68 There are limited head-to-head data comparing BPD with RYGB, but weight loss with BPD is superior to that with LAGB, although rates of diabetes and hypertension improvement at 5.4 years did not differ in 1 study. 110 Scopinaro et al 111 reported a more dramatic effect of BPD on diabetes mellitus among 443 severely obese patients compared with the data in the literature on gastric bypass. The proportion of patients with fasting serum glucose ≤110 mg/dL on free diet and with no therapy was 74% at 1 month, 97% at 1 and 10 years, and 91% at ≥20 years, with the 26% of patients not attaining remission at 1 month being those with the most severe preoperative T2DM.…”
Section: Comparison Among Bariatric Proceduresmentioning
confidence: 87%
“…The bile and pancreatic juices move through the Bbiliopancreatic limb,^which is connected to the side of the intestine close to the end. This supplies digestive juice in the section of the intestine now called the Bcommon limb.^The surgeon varies the length of the common limb to regulate the amount of absorption of protein, fat, and fat-soluble vitamins [31,32]. A recent review demonstrated that also BPD is associated with diminished absorption of lypophilic drugs and thyroxine [31].…”
Section: Discussionmentioning
confidence: 98%